Obtenção e caracterização físico-química dos biodieseis metílico e etílico de algodão (gossypium hirsutum) - Fernandes, David Maikel (2011)
This study also describes the preparation and characterization of cottonseed oil bio-diesels obtained by methyl and ethyl routes. Analysis concerning the rate of saponi-fication, acid value, kinematic viscosity at 40 ° C, peroxide value, and refractive in-dex, among others were also made. The transesterification reaction and ester con-tent were analysed by Thin Layer Chromatography (TLC) and Gas Chromatography (GC), respectively. The consequences of adding the synthetic antioxidant tert-butilhidroquinona (TBHQ) in biodiesels, obtained in relation to the same oxidative stability, was also evaluated. The analysis of the Thermogravimetric (TGA) of vege-table oil and biodiesels obtained and a study of the behavior of Specific Gravity as a function of temperature, by obtaining a mathematical algorithm were also done. De-spite the oxidation stability, all parameters analysed are in accordance with the laws, being also evaluated the possibility of using the ethyl route instead of the methyl route. Were also performed Thermogravimetric Analysis (TGA) of vegetable oil and biodieseis obtained and a study of the behavior of Specific Gravity as a function of temperature, by obtaining a mathematical equation. With the exception of oxidation stability, all parameters are analyzed according to the laws, and also evaluated the possibility of using the route methyl ethyl opposite route. The refined oil used for bio-diesel production showed acid value equal to 0.52 mg KOH g-1, saponification index of 170 mgKOH g-1, kinematic viscosity of 44.2 mm2s-1 and oxidation stability of 19.04 hours. Biodiesel methyl cotton showed average acidity of 0.17 mg KOH g-1 flash point of 170 ° C, density of 883 Kgm-3, oxidation stability of 4.86 hours, the moisture content of 248 mg kg-1 and composition of an ester content of 57.1% ester linoleic (18:2). Biodiesel acid ethyl presented an average of 0.16 mg KOH g-1, flash point of 168 ° C density of 877 Kgm-3, oxidation stability of 4.77 hours, content of moisture in the 372 mg kg-1 and a content of 55.6% linoleic esters in its composition. The yield of product (biodiesel) was measured in the mass of refined oil used and had values of 88% biodiesel to 92% for methyl and ethyl biodiesel. Analysis by gas chromatography (GC) and Thin Layer Chromatography (TLC) showed that the transesterification reaction was carried out for satisfactory, and, in any of the routes used observed the formation of soaps. Although the values of oxi-dation stability are found to low minimum set by law, this can be easily fix with the addition of approximately 200 mg kg-1 of Tert-Butilhidroquinona (TBHQ). TGA curves, along with the moisture content indicated a no significant quantities of water in the final product, indicating biodieseis even when compared to the oil sample de-gradation occurs at a lower temperature to what occurs for this last. Comparing the two routes of production, can be employed to route methyl ethyl op-posite route for biodiesel production of cotton within the limits to be acceptable, to market the product, taking advantage of the benefits that ethanol poses, less toxic, renewable and consolidated production in the country. With the exception of oxidation stability, all data analysis for biodieseis are estab-lished within the legislation, which enhances the use of this material on a commercial basis because of the cotton seed, which is extracted oil, a byproduct of the present process of cultivation of cotton, the fiber being the most important and integral part of higher value added.